Energy conversation in gas separation application using carbon absorption & pressure swing adsorption (PSA) system - Ani, Farid Nasir; Tan, Jaan Soon; Mansor, Muhd. Ridzuan; Yusof, Ahmad Anas (Universiti Teknologi Malaysia, 2004)
Various types of microporous carbon adsorbents have been prepared from Malaysia carbonaceous solid waste, the oil palm shell for the purpose of gas separations. It is an advantage to utilize the precursor by converting into useful adsorbents since it can be obtained easily and abundantly in the country. Chars or carbon molecular sieves (CMS) and activated carbons were prepared in laboratory fluidized and fixed bed reactors by physical and chemical treatments, which included carbonization in nitrogen flow, CO2 activation and chemical impregnation followed by chemical activation. The effects of various processing parameters, such as temperature, hold time and CO2 flow rate on the porosity development have been studied. Besides, different preparation methods, i.e. double - and single - step and chemical agents, i.e. CuCl2 and K2CO3 were used in this study to produce different series of activated carbons. The characterization of microporous carbons was carried out by a static volumetric - physisorption analyzer to determine various characteristic parameters from the analysis of adsorption isotherms. Here, N2 and CO2 have been used as the adsorbates at 77 and 298 K, respectively. Almost all of the carbons appeared to be highly microporous with good and comparable quality activated carbons and chars with CMS characteristics. Single - step CO2 activation was found to be economical and efficient method in preparing activated carbons compared to double - step method. In the separation of CO2 and CH4 binary gas mixture, a laboratory scale PSA - like adsorber system was designed with the use of microporous carbons to adsorb CO2 from the gas stream. The adsorption capacity and kinetic selectivity of CO2 and CH4 on microporous carbon adsorbents were obtained from the breakthrough profiles analysis. The suitable selected activated carbon has shown very good separation of CO2 and CH4, especially at a higher gas flow rate and moderate adsorption pressure in the experiments. CMS produced from oil palm shell for oxygen - selective air separation by simple techniques have followed the Fickian diffusion model in the O2 and N2 adsorption rate testing by volumetric technique. Although the average kinetic selectivity of O2 and N2 for CMS samples prepared was lower than the commercially available CMS, but they have demonstrated fast diffusion rate and comparable capacity for O2 adsorption.